Implementasi Terapi Progressive Muscle Relaxation (PMR) Untuk Menurunkan Kadar Glukosa Darah Dan Stres Pada Pasien Diabetes Mellitus Tipe 2 - Lenggogeni, Devia Putri; Gusty, Reni Prima; Erwanto, Ramadhinda Putri (Universitas Fort De Kock Bukittinggi, 2023)
Hyperglycemia and stress conditions are some of the problems often found in type 2 diabetes mellitus (DM) patients that can worsen the patient's condition. One of the non- pharmacological therapies that can be done to reduce and control blood glucose levels and stress is progressive muscle relaxation (PMR). The implementation of PMR is to determine the effect of PMR therapy on blood sugar levels and stress in patients with type 2 diabetes. The implementation of PMR therapy was carried out for six days every day for 15-30 minutes. Blood sugar levels were measured with a glucometer, and stress was measured with the DASS-42 questionnaire. The results on blood sugar levels was known before the implementation of PMR were 173 mg/dL, while after it was done that blood sugar levels were 98 mg/dL. Furthermore, based on the results of the DASS-42 questionnaire, the patient's stress score before the implementation of PMR was 21, and the stress score after the application of PMR was 15. The results of the implementation of PMR actions showed that PMR therapy is effective in reducing and controlling blood sugar and stress levels of patients with type 2 diabetes, so it can be recommended to patients with type 2 diabetes to apply PMR as additional non-pharmacological therapy to control blood sugar and stress.Keywords: type 2 diabetes mellitus, progressive muscle relaxation, blood glucose, stress